2014
DOI: 10.1002/asia.201403219
|View full text |Cite
|
Sign up to set email alerts
|

Direct Patterning and Biofunctionalization of a Large‐Area Pristine Graphene Sheet

Abstract: Direct patterning of streptavidin and NIH 3T3 fibroblast cells was successfully achieved over a large-area pristine graphene sheet on Si/SiO2 by aryl azide-based photografting with the conventional UV lithographic technique and surface-initiated, atom transfer radical polymerization of oligo(ethylene glycol) methacrylate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…We and others previously shown that surface roughness of submicrometer-scale (>200 nm) elicits accelerated in one case, completely distinctdevelopment of primary hippocampal neurons, by mechanotransductive mechanisms (one or many) that rely strongly on cytoskeletal dynamics (F-actin, in particular). The present results indicate that the roughness generated during by the laser scribing falls into the “active” topographical range previously shown to promote the adhesion and development of primary neurons. , This provides a waiver of using a substrate patterned with different molecules, which would generally require lithographic techniques. …”
supporting
confidence: 54%
“…We and others previously shown that surface roughness of submicrometer-scale (>200 nm) elicits accelerated in one case, completely distinctdevelopment of primary hippocampal neurons, by mechanotransductive mechanisms (one or many) that rely strongly on cytoskeletal dynamics (F-actin, in particular). The present results indicate that the roughness generated during by the laser scribing falls into the “active” topographical range previously shown to promote the adhesion and development of primary neurons. , This provides a waiver of using a substrate patterned with different molecules, which would generally require lithographic techniques. …”
supporting
confidence: 54%
“…Chemically functionalized surfaces have been widely used as a template to understand biological phenomena such as protein–protein interactions and have been applied in biomedical applications including drug delivery systems, anti‐microbials, analytical detection, disease diagnostics, and cell surface engineering 1–4 . Chemical functionalization allows chemically inert substances ( e.g ., graphene, plastics, and metals) to provide suitable properties for relevant applications 5,6 . For example, the immobilization of a DNA aptamer on a gold surface is an initial step to detect a target protein or DNA fragment through surface plasmon resonance (SPR) spectroscopy 7 .…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture and Staining . NIH 3T3 fibroblast cells were maintained in a cell culture medium (Dulbecco's modified Eagle medium supplemented with 10 % fetal bovine serum and 1 % penicillin/streptomycin at 37 °C in a humidified atmosphere containing 5 % CO 2 on tissue culture T25 polystyrene flasks) for allowing continuous growth . The cells were removed from the flask surface by washing twice with 2 mL PBS, followed by incubating in 0.5 mL cell dissociation solution (0.25 % trypsin/EDTA).…”
Section: Methodsmentioning
confidence: 99%